2022
DOI: 10.3390/ma15051742
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Oxide Films Deposited by Sol-Gel Method: Effect of Annealing Temperature on Structural, Optical, and Electrical Properties

Abstract: In our study, transparent and conductive films of NiOx were successfully deposited by sol-gel technology. NiOx films were obtained by spin coating on glass and Si substrates. The vibrational, optical, and electrical properties were studied as a function of the annealing temperatures from 200 to 500 °C. X-ray Photoelectron (XPS) spectroscopy revealed that NiO was formed at the annealing temperature of 400 °C and showed the presence of Ni+ states. The optical transparency of the films reached 90% in the visible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…Partial dehydration of NiAc 2 gives Ni hydroxides and acetates (1−x) Ni(CH 3 COO) 2 ·×Ni(OH) 2 as an intermediate product [ 68 , 69 , 70 ]. It should be noted that the soft bake at 200 °C does not lead to the creation of metal oxides that could interact and create new phases.…”
Section: Resultsmentioning
confidence: 99%
“…Partial dehydration of NiAc 2 gives Ni hydroxides and acetates (1−x) Ni(CH 3 COO) 2 ·×Ni(OH) 2 as an intermediate product [ 68 , 69 , 70 ]. It should be noted that the soft bake at 200 °C does not lead to the creation of metal oxides that could interact and create new phases.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth mentioning that several authors have reported the resistivity values of the NiO x and doped NiO x films in the range of 10 −1 to 10 −3 Ωcm after post-deposition annealing in the temperature range of 400-600 °C (Tyagi et al, 2013;Menchini et al, 2013;Jlassi et al, 2014;Ivanova et al, 2022;Wu and Yang, 2013). The specific values largely depended on the employed deposition methods and the annealing ambient conditions (Jlassi et al, 2014;Pan et al, 2019;Ivanova et al, 2022). A common peculiarity for most of the previous studies is that the as-grown NiO x films were always amorphous and/or exhibited very low crystallinity, independent of the method employed for the film synthesis.…”
Section: Electrical Properties Of Li:nio X Thin Filmmentioning
confidence: 99%
“…NiO x thin films have also been successfully applied as hole transporting layers (HTLs) in organic and perovskite solar cells [ 6 , 7 , 8 , 9 , 10 ], and in inorganic and perovskite light-emitting diodes (LEDs) [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Various methods can be used to prepare NiO thin films, such as RF and DC magnetron sputtering [ 4 , 19 , 20 ], electron-beam evaporation [ 21 ], pulsed laser deposition [ 22 , 23 ], atomic layer deposition [ 24 ], metal-organic chemical vapor deposition [ 25 ], chemical bath deposition [ 26 ], spin coating [ 27 ], sol-gel process [ 28 ], SILAR [ 29 ], and Spray Pyrolysis (SP) [ 30 , 31 ]. Among all these methods, the SP technique has the advantage of being easy and economical because it does not need high vacuum equipment and offers the possibility for large area deposition.…”
Section: Introductionmentioning
confidence: 99%